A hierarchical glucose-intercalated NiMn-G-LDH@NiCo2S4 core–shell structure as a binder-free electrode for flexible all-solid-state asymmetric supercapacitors. Issue 3 (6th January 2020) - Chen, Shixia; Lu, Chengxi; Liu, Lu; Xu, Mai; Wang, Jun; Deng, Qiang; Zeng, Zheling; Deng, Shuguang
Abstract : Flexible, lightweight, and high-energy-density asymmetric supercapacitors (ASCs) are highly attractive for portable and wearable electronics. Abstract : Flexible, lightweight, and high-energy-density asymmetric supercapacitors (ASCs) are highly attractive for portable and wearable electronics. However, the implementation of such flexible ASCs is still hampered by the low specific capacitance and sluggish reaction kinetics of the electrode materials. Herein, a hierarchical core–shell structure of hybrid glucose intercalated NiMn-LDH (NiMn-G-LDH)@NiCo2 S4 hollow nanotubes is deliberately constructed on flexible carbon fiber cloth (CFC). The highly conductive hollow NiCo2 S4 nanotube arrays can not only provide high-speed pathways for ion and electrolyte transfer but also regulate the growth of NiMn-G-LDH nanosheets. The expanded interlayer distance on NiMn-G-LDH nanosheets could further facilitate ion diffusion and improve the rate retention. Benefiting from the rational engineering, the flexible NiMn-G-LDH@NiCo2 S4 @CFC as a free-standing electrode could deliver a superior specific capacity of 1018 C g −1 at 1 A g −1, which is almost twice higher than that of pristine NiCo2 S4 @CFC. In addition, the as-assembled flexible all-solid-state ASC device (NiMn-G-LDH@NiCo2 S4 @CFC//AC) is capable of working at various bending angles and exhibits an impressive energy density of 60.3 W h kg −1 at a power density of 375 W kg −1, as well as a superior cycling stability of 86.4% after 10 000 cycles.